2018
DOI: 10.1016/j.rboe.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities, clinical intercurrences, and factors associated with mortality in elderly patients admitted for a hip fracture

Abstract: ObjectiveTo analyze comorbidities and clinical complications, and to determine the factors associated with mortality rates of elderly patients admitted with a hip fracture in a tertiary public hospital.MethodsSixty-seven medical records were reviewed in a retrospective cohort study, including patients equal to or older than 65 years admitted to this institution for hip fracture between January 2014 and December 2014. The evaluated items constituted were the following: interval of time between fracture and hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 40 publications
2
24
0
6
Order By: Relevance
“…Dementia in particular, was found to be an independent predictor of mortality in our cohort, confirming previously reported findings [ 12 , 16 , 17 ]. Additionally, the presence of pneumonia significantly increased mortality, which was again in line with previous findings [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Dementia in particular, was found to be an independent predictor of mortality in our cohort, confirming previously reported findings [ 12 , 16 , 17 ]. Additionally, the presence of pneumonia significantly increased mortality, which was again in line with previous findings [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a study of nearly 100 000 Medicare patients with vertebral fracture by Lau et al, 7‐year risk of death was nearly doubled in an elderly person with vertebral fracture when compared to elderly counterparts without fracture, after adjustment for comorbidity 12 . Regarding hip fractures, a recent study by Edelmuth et al demonstrated a mortality rate of 11.9% during hospitalization for elderly patients admitted after surgery for hip fracture 13 …”
Section: Discussionmentioning
confidence: 99%
“…As comorbidades clínicas constituem um importante fator de risco para maior mortalidade, além de estarem associadas ao surgimento de complicações pós-cirúrgicas, que podem ser imediatas ou tardias. A avaliação pré-operatória, portanto, deve estar baseada em exame criterioso de toda história clínica do paciente, de modo a estabelecer medidas de prevenção de eventos mórbidos, evitar iatrogenias, definir critérios que alertem para um maior risco e desenvolver enfoque multidisciplinar (Edelmuth, Sorio, Sprovieri, Gali, & Peron, 2018).…”
Section: Idadeunclassified